الفاعلية الثقافية للصور الفنية في رواية عابر سرير لـــ أحلام مستغانمي - كريبع, نسيمة (جامعة الوادي - University of Eloued, 2017)
لقد شهدت الساحة الأدبية انفتاحا على خلفيات معرفية ومؤشرات بنيوية جديدة بعد أن راح الأدب بأجناسه المختلفة يستعير ويستضيف أنواعا أدبية و فنية من غير طبيعته داخل نسيجه اللغوي و فضاءاته الفكرية الثقافية ،وذلك كاستراتيجية تجريبية لتفعيل الحضور الثقافي والفكري داخل نصوصه ،ولا شكّ أنّ الرواية كانت أكثر الأجناس الأدبية استفادة من هذه الظاهرة الاستعارية التفاعلية ؛حيث راحت بقدرتها الاستيعابية تستحضر أشكالا خطابية جديدة من مثل توظيف الفنون في ثناياها توظيفا فنيا ثقافيا بصورة عضوية ،قصد الاستفادة من المضامين الثقافية لتلك الفنون واستثمارها استثمارا سرديا ؛ليتحول النص الروائي إلى أفق فكري ثقافي متفاعل،تماما كما حدث في رواية "عابر سرير" لأحلام مستغانمي (نموذج الدراسة) والتي تحولت إلى ساحة سردية تكتظ بالمرجعيات الثقافية المتداخلة والمنسلة من وراء حضور فن التصوير من خلال التوظيف الذهني السردي لمجموعة من اللوحات التشكيلية و الصور الفوتوغرافية توظيفا فنيا سرديا Abstract:: Literary scene has witnessed open to knowledge backgrounds of new structural and indicators Having claimed the literature various Bojnash borrows hosts kinds of literary and artistic than is normal within the linguistic fabric and Vdhaouath intellectual culture, so a strategy pilot to activate the cultural and intellectual presence inside the texts, no doubt that the novel was more races literary take advantage of this phenomenon interactive Alastarah; which began its ability absorptive conjures new rhetorical forms, such as the employment of the arts within them the main employers technically culturally organically, in order to take advantage of the cultural implications of these arts and invested investment narrative; to turn narrative text to the horizon intellectual Tagafa interactive, just as in the novel "transient bed" to the dreams Mosteghanemi (study model), which turned into a narrative Square packed with cultural Balmarjaaat overlapping Almnslh from behind to attend the art of photography through employment mental narrative of a group of paintings Fine and photographs main employers artistic narrative.
مقال
Keywords: الفاعلية الثقافية ؛ الصور الفنية ؛رواية عابر سرير ؛ أحلام مستغانمي